Application of Bi2Te3 nanomaterial-modified fabric sensors in dance training. (30th September 2020) - Lin, You; Hu, Yifan
Bi2 Te3 has the best thermoelectric merit (ZT) at room temperature. It is ideal for miniature thermoelectric device materials, and is used in mature commercial application. In this study, a commercial fibre-derived conductive fabric sensor based on Bi2 Te3 ministerial was prepared. The conductive fabric sensor shows high sensitivity, excellent selectivity, and good stability. The flexible collection device and the signal transmission components are integrated. For dance training related biomarkers are detected simultaneously, and wearable health monitoring devices are used flexibly. The fibre-derived conductive fabric sensor exhibits high sensitivity, excellent selectivity, good long-term stability and good reproducibility. This research provides new ideas for the application of electrochemical sensors in the field of health monitoring, and has great application value and development potential.